The Influence Of Love Of Money, Machiavellianism, Turnover Intention, And Job Stress On Dysfunctional Behavior With Individual Morality As A Moderating Variable - Puspa Lely Ramadhania; Lilis Ardini; Kurnia (Neo Journal of economy and social humanities, 2023)
An auditor is required to be able to present relevant, accurate and timely information. When acting in the public interest, public accountants must comply with and apply all the basic principles and rules of professional ethics that apply. However, the facts show that there are still many accountants who work without being based on a professional code of ethics. The following research aims to determine the effect of love of money, Machiavellianism, turnover intention, and work stress on dysfunctional behavior with individual morality as a moderating variable. The research approach used in this study uses a quantitative research approach. The results of this study indicate that love of money has an effect on dysfunctional behavior, Machiavellianism has an effect on dysfunctional behavior, turnover intention has an effect on dysfunctional behavior, work stress has an effect on dysfunctional behavior, individual morality moderates love of money on dysfunctional behavior, individual morality does not moderate Machiavellianism on dysfunctional behavior, individual morality moderates turnover intention towards dysfunctional behavior, individual morality moderates work stress towards dysfunctional behavior.